(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the importance of independent education in ensuring the quality of education in higher education institutions, the organization of independent education, the formation of their independent thinking, the knowledge, skills, and qualifications necessary for independent performance of academic work in students and the issues of organization, development, and increase of students’ activity in activities outside the auditorium are highlighted.